PASSIVE AND IONTOPHORETIC PERMEATION OF CAPTOPRIL GEL: AN IN VITRO AND IN VIVO STUDY - Ashish Jain; Satish Nayak; Vandana Soni (Indonesian Journal of Pharmacy, 2012)
The  Objective  of  this  work  was  to  formulate  and evaluate  captopril  gel  to  assess  its  suitability  for  transdermal delivery  by  passive  and  iontophoresis.  A  polymer  gel  was prepared  using  hydroxypropyl  methyl  cellulose  and  in  vitro skin permeability was assessed in full thickness skin of rabbits and  pigs.  For  in  vivo  studies  New  Zealand  rabbits  were  used. In vitro  passive permeation was carried out in Franz diffusion cell but for iontophoresis, diffusion cell was modified according to  Glikfield  design.  Iontophoresis  was  performed  at  a  current density  of  0.5  mA/cm2via  silver  /silver  chloride  electrodes with passive controls but for in vivo  study current density wasreduced  to  0.1  mA/cm2.  Blood  samples  were  analyzed  for drug content by HPLC. Results of the  in vitro  study indicated that iontophoresis considerably increased  the permeation rate of  captopril  compared  to  passive  controls  in  both  the  skin types  (P<0.01).  The  plasma  concentration  of  captopril  was significantly  higher  (P<0.001)  than  that  obtained  in  the passive  controls.  Results  showed  that  the  target  permeation rates  for  captopril  could  be  achieved  with  the  aid  of iontophoresis by increasing the area in an appreciable range.Key words:   Captopril,  iontophoresis,  transdermal,  Rabbit,  Pigskin, in vitro, in vivo.